Genomic feature extraction and comparison based on global alignment of ChIP-sequencing data. Issue 3 (4th May 2017) - Tang, Binhua
ABSTRACT: Enhanced accuracy and high-throughput capability in capturing genetic activities lead ChIP-sequencing technology to be applied prevalently in diverse study for tackling DNA-protein interaction problems. Till now, such questions as deciding suitable ChIP-seq arguments and comparing sample quality still haunt biologists. We propose the methods for answering such questions as deciding optimal argument pairs in global alignment of ChIP sequencing data; then we employ a modern signal processing approach to extract inherent genomic features from the global alignments of transcriptional binding activities; together with pairwise comparison from intra- and inter-sample perspectives; thus we can further determine alignment quality and decide the optimal candidate for multi-source heterogeneous high-throughput sequences. The work provides a practical approach to quantitatively compare the alignment quality for heterogeneous sequencing data, especially in determining the efficiency of transcriptional binding from replicate samples, thus it helps to exploit the potentiality of ChIP-seq for deep comprehension of inherent biological meanings from the high-throughput genomic sequences.